1998
DOI: 10.1097/00003446-199808000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Evoked Response To Acoustic Change Within A Syllable

Abstract: It seems likely that the response to [ei] within the complete syllable reflects changes of cortical activation caused by amplitude or spectral change at the transition from consonant to vowel. The change from aperiodic to periodic stimulation may also produce changes in cortical activation that contribute to the observed response. Whatever the mechanism, the important conclusion is that the auditory cortical evoked potential to complex, time-varying speech waveforms can reflect features of the underlying acous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
155
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(171 citation statements)
references
References 20 publications
10
155
1
5
Order By: Relevance
“…The most likely contributors to the N 100 -P 200 potentials of this study are the vertex-maximal C-potentials which were found to be associated with both sequential and spectral streaming (e.g., Jones et al, 1998;Jones andPerez, 2001, 2002;Jones, 2003), as well as transition from a periodic to an aperiodic sound (Ostroff et al, 1998;Martin and Boothroyd, 1999). The C-potentials appear to reflect a mismatch of temporal and spectral attributes, or their combination (periodicity) between the incoming acoustic change and the preceding stream.…”
Section: Processes Associated With Potentials To Frequency Changementioning
confidence: 69%
See 1 more Smart Citation
“…The most likely contributors to the N 100 -P 200 potentials of this study are the vertex-maximal C-potentials which were found to be associated with both sequential and spectral streaming (e.g., Jones et al, 1998;Jones andPerez, 2001, 2002;Jones, 2003), as well as transition from a periodic to an aperiodic sound (Ostroff et al, 1998;Martin and Boothroyd, 1999). The C-potentials appear to reflect a mismatch of temporal and spectral attributes, or their combination (periodicity) between the incoming acoustic change and the preceding stream.…”
Section: Processes Associated With Potentials To Frequency Changementioning
confidence: 69%
“…The ability to discriminate successive sounds on the basis of frequency is central to the perception of different formants (peak energy bands) of vowels and frequency peaks of consonants (Medwetzky, 2002) and is termed frequency resolution. The N 100 and P 200 have been studied in response to acoustic changes in natural speech associated with phonemes and transitions: fricative to vowel (Ostroff et al, 1998;Friesen and Trembley, 2006), vowel to vowel (Martin and Boothroyd, 2000) and vowel to fricative (Laufer and Pratt, 2003a), and to change in non-speech sounds (Harris et al, 2007(Harris et al, , 2008.…”
Section: Auditory Change Detectionmentioning
confidence: 99%
“…Component N 1 ( 100 ms from stimulus onset) and the immediately following P2 of ERPs have been suggested as a means for studying the initial auditory processing of speech signals (Ostroff et al, 1998;Tremblay et al, , 2003. N 1 -P 2 amplitudes have been related to changes in speech perception accompanying aging , sensory-neural hearing loss (Oates et al, 2002), training-related plasticity (Reinke et al, 2003;Tremblay and Kraus, 2002;Tremblay et al, 2001) and performance decrease by noise masking Whiting et al, 1998).…”
Section: N 1 To Speech and Acoustic Temporal Cuesmentioning
confidence: 99%
“…N 1 -P 2 amplitudes have been related to changes in speech perception accompanying aging , sensory-neural hearing loss (Oates et al, 2002), training-related plasticity (Reinke et al, 2003;Tremblay and Kraus, 2002;Tremblay et al, 2001) and performance decrease by noise masking Whiting et al, 1998). The discrimination of temporal cues in speech has been studied with N 1 as a marker of detecting timevarying changes within a signal (Martin and Boothroyd, 1999) as well as the transition from friction noise to the following vowel (Ostroff et al, 1998;Tremblay et al, 2003). The ability of the auditory system to encode temporal cues is critical for many auditory functions including speech perception and localization.…”
Section: N 1 To Speech and Acoustic Temporal Cuesmentioning
confidence: 99%
“…The P1-N1-P2 response, also called the acoustic change complex, is a physiological response that signals the neural detection of acoustic change at the level of the auditory cortex and corresponds well with perceptual thresholds for the same acoustic change (Kaukoranta, Hari, & Lounasmaa, 1987;Martin & Boothroyd, 1999;Ostroff, Martin, & Boothroyd, 1998). Therefore, the P1-N1-P2 is particularly well suited for studying a number of acoustic cues important for the perception of speech, including silent gaps.…”
mentioning
confidence: 99%